2021
DOI: 10.1002/jsfa.11584
|View full text |Cite
|
Sign up to set email alerts
|

Improving the nutritional value and digestibility of wheat straw, rice straw, and corn cob through solid state fermentation using different Pleurotus species

Abstract: BACKGROUND:The growing food-feed-fuel competition, declining availability of traditional feeds, higher prices, and the urgent need to provide long-term sustainability for animal production have all triggered global research into the optimum extraction of energy and nutrients from lignin-rich plant biomass. Recent studies have shown that the Pleurotus species of white rot fungus can selectively degrade lignin in lignin-rich plant biomass; however, its effectiveness in selectively degrading lignin depends on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 36 publications
9
22
0
Order By: Relevance
“…ostreatus were markedly higher than both the control and the other treatments. Similar results were obtained by Sufyan et al 71 where the nutritional value and digestibility of wheat straw, rice straw, and corn cob using Pleurotus species improved.…”
Section: Resultssupporting
confidence: 89%
“…ostreatus were markedly higher than both the control and the other treatments. Similar results were obtained by Sufyan et al 71 where the nutritional value and digestibility of wheat straw, rice straw, and corn cob using Pleurotus species improved.…”
Section: Resultssupporting
confidence: 89%
“…Several biological methods have been reported in processing high crude fiber forage in order to increase nutritional content and its digestibility. Sufyan et al (2022) reported that delegitimated fungi have potential to decrease lignin content in some crop residues and agro-based byproduct. They studied the effect of three species of Pleurotus in delignification of wheat straw, rice straw and corn cob.…”
Section: Introductionmentioning
confidence: 99%
“…(FAO, 2016). In addition to carbohydrates, fat and protein, rice also includes a respectable quantity of iron, calcium, thiamine, riboflavin and niacin (Sufyan et al, 2022). Pakistan supplies highquality rice to Saudi Arabia, West African nations, Malaysia, Bangladesh, Iran and Indonesia.…”
Section: Introductionmentioning
confidence: 99%